2000
DOI: 10.1002/1097-0096(200009)28:7<340::aid-jcu4>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of acute colonic diverticulitis: The ?dome sign?

Abstract: Purpose This study was performed to clarify the sonographic features of acute colonic diverticulitis to enable its differentiation from appendicitis. Methods Of 119 patients who were referred to our hospitals for lower abdominal pain between June 1997 and December 1998 and underwent sonography, 12 patients had a definitive diagnosis of acute colonic diverticulitis and 4 patients a tentative diagnosis. Seventy‐eight patients were diagnosed as having acute appendicitis, confirmed by appendectomy. In the 16 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
13
0
5
Order By: Relevance
“…In recent years, bowel ultrasound has gained importance as a reliable and non‐invasive imaging modality for the diagnostic work‐up and clinical follow‐up of patients with some inflammatory bowel disorders, such as Crohn's disease, appendicitis and diverticulitis 5–16 . This can be attributed to the technological advancement of ultrasound equipment which has greatly improved the resolution capability, with good cross‐sectional imaging of the gut wall and display of the surrounding mesentery, thus making it possible to detect the transmural extent of inflammation 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, bowel ultrasound has gained importance as a reliable and non‐invasive imaging modality for the diagnostic work‐up and clinical follow‐up of patients with some inflammatory bowel disorders, such as Crohn's disease, appendicitis and diverticulitis 5–16 . This can be attributed to the technological advancement of ultrasound equipment which has greatly improved the resolution capability, with good cross‐sectional imaging of the gut wall and display of the surrounding mesentery, thus making it possible to detect the transmural extent of inflammation 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Most existing trials have focused mainly on specific disease entities (i.e. Crohn's disease, ulcerative colitis, appendicitis, diverticulitis) 5–16 . In particular, in many of these reports, ultrasound was performed under optimal conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) In contrast to other guidelines the CDD for the first time favors abdominal US as the method of choice for cross sectional imaging. Because published work for now more than 25 years and the excellence of few individuals, etching the standing of US in their institutions in stone [2][3][4][5][6][7][8][9], may not represent general standards of US for diverticulitis, this paper attempts to outline the fundamental characteristics of diverticulitis at US as well as their technical and personal prerequisites against the back-…”
mentioning
confidence: 99%
“…Reports about detection of fecoliths on plain radiography are anecdotal [10,11]. On ultrasound typical hypo-or anechoic structures protruding from the colonic wall ("dome"-sign) can be found in diverticulitis [12]. A recent study showed a high sensitivity and specificity of ultrasound to diagnose right-colonic diverticulitis.…”
mentioning
confidence: 99%